The Multifaceted Applications of Telemedicine in Contemporary Healthcare: Review of Its Impact on Pediatrics, Dermatology, Psychiatry, and Anesthesia - Kariry, Khaleel Yahia Hassan; Alshammari, Fahad Tulayhan Mohammad; Maswdi, Ahmed Mohsen Mohammed; Alwadai, Mesfer Saleh Mari; Kurdi, Ahmed Saad; Fallatah, Khulood Yahya; Al-Ahmadi, Majed Mohammed Ahmed; Alharbi, Mubarak Nassar Shobikan; Almuhanna, Abdulmohsen Abdullatif; Hakami, Naeem Mohammed; Al-Soqair , Sara; Alanazi , Hamdan Saad; et al. (Journal of Ecohumanism, 2024)
Background: Telemedicine has emerged as a transformative force in modern healthcare, enhancing access to medical services across various specialties, including pediatrics, dermatology, psychiatry, and anesthesia. This technology addresses barriers related to geography and financial constraints, improving health outcomes for diverse populations. Methods: This review systematically analyzes current literature on telemedicine applications across the aforementioned specialties. It highlights technological advancements, implementation strategies, and outcomes related to patient care. Data were sourced from peer-reviewed journals, clinical studies, and healthcare reports to provide a comprehensive overview of telemedicine’s efficacy and challenges. Results: Findings indicate that telemedicine significantly improves access to care, particularly in underserved areas. In pediatrics, it allows for remote consultations, enhancing the management of chronic illnesses. In dermatology, telemedicine facilitates timely diagnosis through virtual assessments. For psychiatry, it offers a vital platform for mental health interventions, reducing barriers to treatment. In anesthesia, telemedicine supports pre-operative assessments and post-operative follow-ups, ensuring patient safety and satisfaction. Conclusion: The integration of telemedicine into healthcare delivery across pediatrics, dermatology, psychiatry, and anesthesia demonstrates its potential to enhance patient care, increase efficiency, and reduce healthcare costs. Continued investment in telemedicine technologies and training for healthcare professionals is essential for maximizing these benefits.